A Retrospective study on fracture of the mandible in the D.O.P.D of Rangpur Medical College Hospital. - Md Hafizul Islam; Mohammad Sayeed Ahmed; Asik Rayhan; Ashraful Hayat (Update Dental College, 2016)
Aims and 0bjective of present study: A retrospective study was performed involving 480 patients of fracture mandible who were attended in dental O.P.D of Rangpur Medical College Hospital during the period 2010 to December 2013. The aims of this study to analyze the fracture mandible cases and treatment modality by miniplate osteo synthesis. To evaluate causes, sites and different ages of fracture of mandible. Methods: Retrospective study of data were collected from the patients record file of dental O.P.D during the period January 2010 to December 2013. Result: A total of 480 cases were studied where miniplate immobilization were made in 288 cases. Arch bar immobilization were made in 144 cases and rest 48 cases eyelet wiring. Among the 288 case male female ratio was 2:1. The treatment modality relation to patient was same in number for male patients by mini plate immobilization where as arch bar immobilization was same for female patient in number. The reason behind may be due to fear of operation by female patient. The results are shown in pie chart and bar diagram. Conclusion: Using this research results, a great effort was made to provide better management of fracture mandible patient to the population of at or around the city of Rangpur.Mandibular fracture were more present in male between 20 to 30 years rta was about 50% cases. Rigid internal fixation by monocortical mini plate osteo synthesis provide good long time results and satisfactory cosmosis without any significant sequela[8].The more frequently affected region were symphysis menti and angle of mandible. Update Dent. Coll. j: 2016; 6 (1): 30-34